The Emotional Experience of Sustainability Courses: Learned Eco-Anxiety, Potential Ontological Adjustment. (September 2020) - Graham, Peter; Kuyvenhoven, Cassandra; Upitis, Rena; Arshad-Ayaz, Adeela; Scheinman, Eli; Khan, Colin; Goebel, Allison; Brown, R. Stephen; Hovorka, Alice
The knowledge content of university-level introductory sustainability courses elicits emotional reactions by students that are novel within the typical classroom context. Common negative reactions include 'sadness', 'worry', 'guilt' and 'disgust', while more positive responses include 'feeling angry', 'empowered', 'like trying to make a difference' or 'having raised awareness'. These emotions are indexical of a deeper social epistemic collision between historically established social identities, including behavioural scripts consistent with, and generative of, unsustainability on the one hand, and a growing collective awareness of the consequent unsustainability that threatens students' future well-being on the other. The authors argue that introductory sustainability courses set up the potential for not only a learned eco-anxiety, but also an ontological adjustment. That adjustment might bring student, historical inheritance and environment from a state of living in a suffering, but still separate, world to a practice of becoming with a world into which we extend and that also extends into us. Therefore, it is arguably important for instructors to be aware of the possibility of students getting into a negative state of eco-anxiety and for instructors to also have some tools for supporting a more positive ontological adjustment. We recommend that they become skilled in facilitating transformational learning by including some discussions about the ontology of self in any introductory sustainability instruction. Directing students' attention to their own emotional responses can also be useful for grounding such classroom discussions and transformational learning.